Case report: Exploring chemoradiotherapy-induced leukoencephalopathy with 7T imaging and quantitative susceptibility mapping - Celardo, Gaetano; Scaffei, Elena; Buchignani, Bianca; Donatelli, Graziella; Costagli, Mauro; Cristofani, Paola; Canapicchi, Raffaello; Pasquariello, Rosa; Tosetti, Michela; Battini, Roberta; Biagi, Laura (Frontiers in Neurology, 2024)
Chemotherapy and radiotherapy are widely used in the treatment of central nervous system tumours and acute lymphocytic leukaemia even in the paediatric population. However, such treatments pose run the potential risk of a broad spectrum of cognitive and neurological deficits. Even though the correlation with cognitive decline is still not clear, with neuroradiologicalclear, neuroradiological correlates defects indicating outcomes of complex leukoencephalopathy, linked to including white matter injury and vasculopathies may be identified. The correlation between brain damage and cognitive decline has, as yet, not been fully elucidated, and the molecular mechanisms determining the long-term effects of chemotherapy and radiotherapy are still not entirely understood. However, it has been established that the effects of both therapies are additive and doses exceeding 25 Gy can lead to long-term or chronic brain damage. Thanks to the use of ultra-high field (UHF)7T MRI it is possible to better define the vascular pattern of the brain lesions with the added advantage of identifying their characteristics and anatomical localization, which, however, are not evident with a conventional brain scan. Moreover, the use of Quantitative Susceptibility Mapping (QSM), a more targeted technique, makes it possible to discriminate between calcium deposits on vessels (chemoradiation-induced) and haemoglobin deposition in radio-induced cavernomas, speculating, as a result, about the pathophysiology of iatrogenic brain damage. Interestingly, this case report gives meaningful insights into the feasibility and putative advantages of UHF MRI to study chemo and radiation-induced damage in the paediatric population. We describe the case of a 9 years-old child boy with a T-type acute lymphoid leukaemia who had previously been treated with polychemotherapy and high-dose RT. To better define the child's neuroradiological pattern, 7T MRI and QSM were performed in addition to conventional imaging examinations. Our case report suggests the potential usefulness of a QSM study to distinguish radio-induced vascular malformations from mineralizing microangiopathy.